A Bibliometric Study on the Impact of Teaching Material Utilization in Quantum Physics Instruction Using the Problem-Based Learning Models - Putri Nabila; Hidayati (Universitas Negeri Padang, 2025)
Quantum physics presents significant conceptual challenges due to its abstract nature and incompatibility with students’ everyday logic, often resulting in misconceptions and low conceptual understanding. Teaching materials that are not contextually grounded and conventional instructional models further exacerbate the difficulty of quantum physics learning. Considering the importance of mastering quantum concepts in higher education, particularly in preparing future physics educators, innovative teaching approaches are urgently needed. This study aims to investigate research trends on the use of contextual teaching materials in quantum physics instruction employing Problem-Based Learning (PBL) models through bibliometric analysis. By analyzing 100 articles from 2015 to 2025 using Publish or Perish and VOSviewer, this study identifies dominant research focuses, including the role of analogies, PBL modules, and immersive technologies in enhancing conceptual understanding. The results are expected to inform future developments in quantum physics education by highlighting effective pedagogical strategies supported by teaching materials and student-centered learning models.